2013
DOI: 10.1155/2013/717546
|View full text |Cite
|
Sign up to set email alerts
|

In VivoHealthy Knee Kinematics during Dynamic Full Flexion

Abstract: Healthy knee kinematics during dynamic full flexion were evaluated using 3D-to-2D model registration techniques. Continuous knee motions were recorded during full flexion in a lunge from 85° to 150°. Medial and lateral tibiofemoral contacts and femoral internal-external and varus-valgus rotations were analyzed as a function of knee flexion angle. The medial tibiofemoral contact translated anteroposteriorly, but remained on the center of the medial compartment. On the other hand, the lateral tibiofemoral contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 19 publications
(32 reference statements)
4
42
0
Order By: Relevance
“…21,22 Known as the "screw-home" mechanism, the coupling between axial rotation and flexion-extension is also recognized in the human knee under passive conditions. 23,24 In-vivo, internal tibial rotation during deep knee flexion in humans has been reported 11,12 ; however, this pattern is not typically recognized during activities requiring greater knee extension such as walking. 19,20 We found internal rotation to be significantly correlated with knee flexion in the majority of dogs, and while a direct comparison cannot be made between species with our study design, it would appear that the "screw-home" mechanism is more prominent in dogs when compared to what has been observed in humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,22 Known as the "screw-home" mechanism, the coupling between axial rotation and flexion-extension is also recognized in the human knee under passive conditions. 23,24 In-vivo, internal tibial rotation during deep knee flexion in humans has been reported 11,12 ; however, this pattern is not typically recognized during activities requiring greater knee extension such as walking. 19,20 We found internal rotation to be significantly correlated with knee flexion in the majority of dogs, and while a direct comparison cannot be made between species with our study design, it would appear that the "screw-home" mechanism is more prominent in dogs when compared to what has been observed in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Normal kinematic parameters of the knee in humans vary widely over a range of different daily activities; unfortunately, equivalent information for the canine knee is sparsely reported. High‐precision 3D in‐vivo knee kinematics in normal dogs has been described in two experimental studies .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The kinematics of the native knee have been widely investigated (21). Previous studies have reported several features of axial rotation in the native knee.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D surface geometries of the femur, tibia and patella were reconstructed and aligned in the same manner as the 2D measurement technique. Model-image registration was performed to measure patellar kinematics, which were taken as reference values, using custom open-source software (JointTrack, Gainesville, FL, USA, www.sourceforge.net/projects/jointtrack) [20]. Differences in the root-mean-square (RMS) errors between biplane images with 3D bone models and sagittal plane patellar kinematics measurements were less than 2.0°and 3.0 mm, for in-plane rotation and translations, respectively.…”
Section: Methodsmentioning
confidence: 99%